The plasma characteristics of femtosecond-nanosecond dual-pulse laser ablated soil - Shangyong Zhao; Chao Song; Xun Gao; Kaimin Guo; Zuoqiang Hao; Jingquan Lin (Results in Physics, 2020)
We report on the observation of dual-pulses laser-produced plasmas (DP-LPPs), following a femtosecond Ti: sapphire pulse laser ablate soil generated a substantial number of soil aerosol particle clusters of soil target and then a nanosecond Nd:YAG pulse laser re-ablated the soil aerosol particles clusters. The temporal evolution of the fs laser-produced plasmas (fs-LPPs) highlight a different in plasma plume expansion dynamics and particles clusters distributions where, the initial position and velocity of plasma plume expansion are 0.79 mm and 4.8 km/s, the terminal position is 2.2 mm and the velocity gradually become slower and slower, in the delay time range of 150 ns to 2.1 μs. There are three distribution states contains a columnar particle fluid flow region, “Mushroom cloud” fluid flow region, and arbitrary shape fluid flow region of the particles scattering images of different inter-pulse time at 1, 5, 9, 10, 30, 50, 200, 400 and 800 μs. Based on the Boltzmann plot method and Stark broadening, the plasma temperature and electron density is also investigated, the results shows that DP-LPPs optical emission spectrum (OES) has a narrow linear broadening and enhanced spectral intensity, associates with the higher plasma temperature and lower electron density compare with the single fs-LPPs.